MANAGEMENT OF VILLAGE-OWNED ENTERPRISES (BUMDES) AMANAH IN PLANTATION UNITS IN PELALAWAN REGENCY - Sri Fitri Indayani; Mayarni (ADISAM Publisher, 2022)
Management of Village Owned Enterprises (BUMDes) The Plantation Unit is a village business institution managed by the community and village government in an effort to strengthen the village economy and is formed based on the needs and potential of the village. This study aims to determine how the Management of Village Owned Enterprises (BUMDes) Amanah at the Plantation Unit in Pelalawan Regency. Data was collected by direct interviews, observation and documentation related to the research. The research method used is descriptive qualitative research. Then data analysis with data collection, data reduction, data presentation and drawing conclusions. Based on the research conducted by the authors, the results and conclusions are as follows: first, in its implementation the BUMDes Amanah has a management mechanism and is implemented well, seen from the planning stage, it has followed the procedures and planned the program to be run and managed, the organization has shown managers who are elements of the village community. , mobilization has moved members to achieve success and its implementation every 3 months. Second, the supporting factors are business capital and facilities and infrastructure.